2015
DOI: 10.1155/2016/5720758
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Left Ventricular Hypertrophy and Stem Cells: Current Evidence and New Perspectives

Abstract: Left ventricular hypertrophy (LVH) is a strong predictor of adverse cardiovascular outcomes. It is the result of complex mechanisms that include not only an increase in protein synthesis and cell size but also proliferating cardiac progenitor cells and the influx of bone marrow-derived cells developing into cardiomyocytes. Stem and progenitor cells are known to contribute to the renewal of adult mammalian cardiomyocytes in case of myocardial injury or pressure and volume overload. They are activated in LVH and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 87 publications
1
46
0
Order By: Relevance
“…Although our study focuses on cell-autonomous effect of Chaer on cardiomyocyte hypertrophy, the cardiac effect of Chaer expression may also involve other cellular process in non-myocyte cardiac cells. It is intriguing that FISH assay detected significant signal of Chaer within the mouse epicardium where potential progenitor cells for endothelium and fibroblasts have been reported to reside 54 , and Chaer KO significantly reduced TAC induced cardiac fibrosis. It is also interesting to observe that a significant number of cell cycle genes are regulated by Chaer .…”
Section: Discussionmentioning
confidence: 99%
“…Although our study focuses on cell-autonomous effect of Chaer on cardiomyocyte hypertrophy, the cardiac effect of Chaer expression may also involve other cellular process in non-myocyte cardiac cells. It is intriguing that FISH assay detected significant signal of Chaer within the mouse epicardium where potential progenitor cells for endothelium and fibroblasts have been reported to reside 54 , and Chaer KO significantly reduced TAC induced cardiac fibrosis. It is also interesting to observe that a significant number of cell cycle genes are regulated by Chaer .…”
Section: Discussionmentioning
confidence: 99%
“…Many factors could induce ventricular hypertrophy, such as Ang-II, ET-1, catecholamines, growth factors and TNF-a [30]. Among them, Ang-II is commonly used for induction of hypertrophic models, as it can potently induce pressure overload, which leads to an increase in wall thickness and concentric hypertrophy of the left ventricle as a compensatory mechanism to maintain the ventricular EF under conditions of increased peripheral resistance [31]. In the present study, we investigated the role of CD38 in the development of Ang-II-induced cardiac hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…However, the migration ability of transplanted cells onto the heart was not addressed. Experimental studies have shown that an increase in preload results in the mobilization of progenitor cells from the bone marrow and migration into the heart, which plays an important role in cardiac hypertrophy [51]. Thus, we can not exclude the possibility of stem cells from the bone marrow in modulating ventricular hypertrophy.…”
Section: Discussionmentioning
confidence: 97%